Making and faking kinship : marriage and labor migration between China and South Korea - Freeman, Caren, 1968- (Cornell University Press, 2011)
In the years leading up to and directly following rapprochement with China in 1992, the South Korean government looked to ethnic Korean (Chosǒnjok) brides and laborers from northeastern China to restore productivity to its industries and countryside. South Korean officials and the media celebrated these overtures not only as a pragmatic solution to population problems but also as a patriotic project of reuniting ethnic Koreans after nearly fifty years of Cold War separation. As Caren Freeman's fieldwork in China and South Korea shows, the attempt to bridge the geopolitical divide in the name of Korean kinship proved more difficult than any of the parties involved could have imagined. Discriminatory treatment, artificially suppressed wages, clashing gender logics, and the criminalization of so-called runaway brides and undocumented workers tarnished the myth of ethnic homogeneity and exposed the contradictions at the heart of South Korea's transnational kin-making project. Unlike migrant brides who could acquire citizenship, migrant workers were denied the rights of long-term settlement, and stringent "as restricted their entry. As a result, many Chosǒnjok migrants arranged paper marriages and fabricated familial ties to South Korean citizens to bypass the state apparatus of border control. Making and Faking Kinship depicts acts of "counterfeit kinship," false documents, and the leaving behind of spouses and children as strategies implemented by disenfranchised people to gain mobility within the region's changing political economy.